Resistance of SARS-CoV-2 variants to neutralization by convalescent plasma from early COVID-19 outbreak in Singapore - Wang, Bei (2021)
The rapid spreading of SARS-CoV-2 variants B.1.1.7 originated from the United Kingdom and B.1.351 from South Africa has contributed to the second wave of COVID-19 cases in the respective countries and also around the world. In this study, we employed advanced biochemical and virological methodologies to evaluate the impact of Spike mutations of these strains on the degree of protection afforded by humoral immune responses following natural infection of the ancestral SARS-CoV-2 strain during the early stages of the outbreak. We found that antibody-mediated neutralization activity was partially reduced for B.1.1.7 variant and significantly attenuated for the B.1.351 strain. We also found that mutations outside the receptor-binding domain (RBD) can strongly influence antibody binding and neutralization, cautioning the use of solely RBD mutations in evaluating vaccine efficacy. These findings highlight an urgent need to develop new SARS-CoV-2 vaccines that are not based exclusively on the ancestral SARS-CoV-2 Spike gene sequence.